2000
DOI: 10.1073/pnas.210395297
|View full text |Cite
|
Sign up to set email alerts
|

Manifold anomalies in gene expression in a vineyard isolate of Saccharomyces cerevisiae revealed by DNA microarray analysis

Abstract: Genome-wide transcriptional profiling has important applications in evolutionary biology for assaying the extent of heterozygosity for alleles showing quantitative variation in gene expression in natural populations. We have used DNA microarray analysis to study the global pattern of transcription in a homothallic strain of Saccharomyces cerevisiae isolated from wine grapes in a Tuscan vineyard, along with the diploid progeny obtained after sporulation. The parental strain shows 2:2 segregation (heterozygosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 32 publications
8
144
0
1
Order By: Relevance
“…Synergistic expression of cellulase genes for degradation of cellulosic substrates has been demonstrated by various studies (7,(99)(100)(101), and growth on cellulose has been accomplished through co-expression of cellulase genes in S. cerevisiae (102). Various hypotheses have been proposed to explain the mechanism of synergistic interactions, however research has shown that the extent of cellulase synergism is influenced by enzyme concentration and the nature of the lignocellulosic substrate (65), therefore synergism is dependent on the ratio of individual enzymes, the substrate saturation and the properties of the substrate (99).…”
Section: Synergism Conceptmentioning
confidence: 99%
“…Synergistic expression of cellulase genes for degradation of cellulosic substrates has been demonstrated by various studies (7,(99)(100)(101), and growth on cellulose has been accomplished through co-expression of cellulase genes in S. cerevisiae (102). Various hypotheses have been proposed to explain the mechanism of synergistic interactions, however research has shown that the extent of cellulase synergism is influenced by enzyme concentration and the nature of the lignocellulosic substrate (65), therefore synergism is dependent on the ratio of individual enzymes, the substrate saturation and the properties of the substrate (99).…”
Section: Synergism Conceptmentioning
confidence: 99%
“…This can be explained partly by the presence of a high degree of protein polymorphism observed by electrophoresis at many loci (24,78). Recent studies have also shown that there is a large amount of variation in the level of gene expression among different alleles at a locus (79)(80)(81)(82)(83). In humans, it has been reported that, in 63% of the genes examined, the expression level of one allele is 2-fold or more greater than that of another allele (81).…”
Section: Polymorphism In Cis-regulatory Regions Andmentioning
confidence: 99%
“…Genome-wide measurements have revealed high rates of genetic variation in gene expression (typically 410% of genes) in humans (Enard et al, 2002;Rockman and Wray, 2002;Bray et al, 2003;Lo et al, 2003;Whitney et al, 2003;Morley et al, 2004;Pastinen et al, 2004;Radich et al, 2004), mice (Cowles et al, 2002;Schadt et al, 2003;Shockley and Churchill, 2006), fish (Oleksiak et al, 2002(Oleksiak et al, , 2005, flies (Jin et al, 2001;Wayne and McIntyre, 2002;Meiklejohn et al, 2003;Rifkin et al, 2003;Nuzhdin et al, 2004;Ranz et al, 2004), yeast (Cavalieri et al, 2000;Brem et al, 2002;Townsend et al, 2003;Yvert et al, 2003;Fay et al, 2004), plants (Kirst et al, 2005;Vuylsteke et al, 2005;Lai et al, 2006) and bacteria (Le et al, 2005). Patterns of expression divergence have also been compared between sexes (Jin et al, 2001;Ranz et al, 2003;Gibson et al, 2004), across developmental stages (Rifkin et al, 2003), among tissue types (Enard et al, 2002;Whitehead and Crawford, 2005;Khaitovich et al, 2005a, b) and over different environments (Fay et al, 2004;Landry et al, 2006).…”
Section: Genomic Variation In Gene Expressionmentioning
confidence: 99%